2013
DOI: 10.1103/physrevb.88.214512
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced 0-πtransitions and supercurrent crossover in antiferromagnetic weak links

Abstract: We compute self-consistently the Josephson current in a superconductor-antiferromagnet-superconductor junction using a lattice model, focusing on 0 − π transitions occurring when the width of the antiferromagnetic region changes from an even to an odd number of lattice sites. Previous studies predicted 0 − π transitions when alternating between an even and an odd number of sites for sufficiently strong antiferromagnetic order. We study numerically the magnitude of the threshold value for this to occur, and als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…For an odd number of chains in the antiferromagnet, there will be a net magnetization proportional to the number of sites on each chain. Such an uncompensated interface with a net magnetization allows for interesting properties not found in compensated interfaces [11,12,14]. Assuming translational invariance in the 𝑧direction, the Fourier-transformed Hamiltonian may be written in compact matrix form…”
Section: Introductionmentioning
confidence: 99%
“…For an odd number of chains in the antiferromagnet, there will be a net magnetization proportional to the number of sites on each chain. Such an uncompensated interface with a net magnetization allows for interesting properties not found in compensated interfaces [11,12,14]. Assuming translational invariance in the 𝑧direction, the Fourier-transformed Hamiltonian may be written in compact matrix form…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the potential of using antiferromagnets in superconducting spintronics has been recognized. For instance, at the interface between an antiferromagnet and a superconductor, normal reflection and AR have been demonstrated to be both specular and retroreflective [49][50][51][52][53][54][55][56][57][58][59][60][61][62]. In heterostructures, these anomalous processes fundamentally change the behaviour of the electrical and thermal conductance [49].…”
mentioning
confidence: 99%
“…In heterostructures, these anomalous processes fundamentally change the behaviour of the electrical and thermal conductance [49]. In Josephson junctions, atomic-scale 0 − π transitions [51][52][53][54][55][56] are predicted to occur. The existence of Josephson effects has been experimentally verified [57][58][59][60][61][62], but the remaining theoretical predictions have yet to be explored.…”
mentioning
confidence: 99%
“…It has been theoretically shown that AF-S junctions exhibit additional scattering processes different from those in N(F)-S junctions [56]. In Josephson junctions, these new scattering processes create low-energy bound states [57] that lead to anomalous phase shifts [58] and atomic-scale 0−π transitions [59][60][61][62]. On the other hand, although the existence of Josephson supercurrents in S-AF-S junctions has been experimentally reported [63][64][65][66][67][68], other theoretical predictions have yet to be explored.…”
mentioning
confidence: 99%